2016
DOI: 10.1039/c5pp00349k
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Fries rearrangement of aryl acetamides: regioselectivity induced by the aqueous micellar green environment

Abstract: Photochemical reactions tend to give more than one photoproduct. However, such a reaction can be a powerful synthetic tool when it is possible to conduct it in regioselective conditions yielding a single photoproduct. Water-surfactant solutions as reaction media can be considered as an approach in this context because they show products with different features than those from isotropic solutions. Here we describe results obtained from studying the effect on the prototypical photoreaction, known as the photo-Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 73 publications
(1 reference statement)
4
28
0
Order By: Relevance
“…In addition, we have also contributed to show how important is the application of the photo‐Fries rearrangement reaction in the preparation of 2,2‐dimethyl‐4‐chromanone derivatives (33,34) and carbazole derivatives (35,36). Recently, we were able to show the selectivity and the effect of surfactant micelles on the photo‐Fries reaction of an assortment of substituted acetamides (37) as well as substituted aryl benzoates (38) and also, the photochemical behavior of 3‐aryloxy estrone derivatives in solution (39).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we have also contributed to show how important is the application of the photo‐Fries rearrangement reaction in the preparation of 2,2‐dimethyl‐4‐chromanone derivatives (33,34) and carbazole derivatives (35,36). Recently, we were able to show the selectivity and the effect of surfactant micelles on the photo‐Fries reaction of an assortment of substituted acetamides (37) as well as substituted aryl benzoates (38) and also, the photochemical behavior of 3‐aryloxy estrone derivatives in solution (39).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the confined environment provided by the hydrophobic core of the micelle can be considered as a micro reactor where (photo)reactions can take place, the reactivity of radical species generated can be controlled and, at the same time, can be helpful to direct the selectivity of the (photo)products. Some interesting examples of photoreaction carried out in micellar media as optimal micro reactor that can control the selectivity and yield of the photoproducts can be found in the literature [42][43][44][45] and our research group has also contributed with several examples [46][47][48][49].…”
Section: Graphic Abstractmentioning
confidence: 99%
“…In this regard, UV-visible spectroscopy studies of 3-acylestrone derivatives (1-3) in micellar solution were conducted in order to determine the binding constant (K b ) between the surfactants (SDS, CTAC and Brij-P35) and the steroids 1-3. The methodology employed in this study has been previously reported for the determination of binding constants of aryl acetamide and aryl benzoates [46,47]. The analysis of bathochromic and hyperchromic shifts of the lower energy absorption band of the steroids 1-3 in water by addition of increasing amounts of surfactant led to evaluate the extent of binding of steroids to the surfactants within the hydrophobic core of the micelle (batho-and hyperchromic shifts, see Figures S5-S7 in Supporting Information).…”
Section: Binding Constants (K B ) Of 3-acylestrone (1 and 2) And 3-acetyl-17-norestrone (3) In Micellar Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] Compared to its thermal version, the Lewis-acid catalyzed Fries rearrangement, PFR has an additional benefit of being a greener synthetic route, since it can be achieved under milder conditions. 3,14,15 Given its importance for synthesis, it is not surprising that PFR has been the subject of numerous investigations in the past. Nevertheless, the conceptual theoretical knowledge of this reaction is still incipient [36][37][38] and, as we shall see, even the full set of electronic states involved in the reaction has not been yet identified.…”
Section: Introductionmentioning
confidence: 99%